Change at home, in the labor market, and on the job - Polachek, Solomon W.; Tatsiramos, Konstantinos (Emerald Publishing Limited, 2020)
How do changes at home, in the labor market and on the job affect worker well-being? This volume of Research in Labor Economics contains eight original and insightful articles answering this question. Seven deal with demographic and labor market change, and one deals with wage differences essentially at a point in time. Of the seven, two articles analyze changes in family related matters and have implications regarding labor supply; two examine legislative changes, one of which has implications on teenage employment, and the other on informal business formation; one looks at potential productivity changes on farms in a developing country and has implications for remaining on the family farm or going to work; one models wage growth and shows why wages sometimes fall as one remains in a job longer; and finally, one investigates new enterprise formation over time.
Includes index.
Keywords: Labor market.; Business & Economics -- Labor.; Employment & unemployment.; elektronické knihy; electronic books